A STUDY IN SITOLOGIA IN ROMAN EGYPT - El Mosallamy, Dr. Abdalla H. S. (مجلة كلية الاداب, 1975)
Aurelius Victor tells us that in the time of Augustus cox Aegypto urbi annona ducenties centena milia frumenti in webantur” (1). It is evident that still greater revenue came in Rome after the hieratic lands had been confiscated and the Canals put in good working order. It seems, any how, that this amount remained approximately the same along the Roman nule : “ de urbe Alexandrinorum et Aegyptiacis provinciis 8. Felici frumenti missione octogies centena milia complente ”(). This amount of corn, besides about quarter a billion Roman denarii, (3), may justify the fact that the Emperor of Rome considered Exypt the great possession of himself(4), though he said “ Aegyptum imperio populi romani adieci ”(5). Egypt was put by the Emperor in a singular position (6).